Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.20452/pamw.16102
|View full text |Cite
|
Sign up to set email alerts
|

Thromboprophylaxis in hospitalized COVID-19 patients: the efficacy and safety of the approved hospital protocol

Abstract: This study aimed to assess the efficacy and safety of the approved in our Hospital thromboprophylaxis algorithm. Thrombotic events, with higher than usual occurrence, are commonly reported in COVID-19 patients. Until now limited data exist to guide the intensity of antithrombotic prophylaxis. We declare that the risk of arterial and venous thromboembolic events in COVID-19, according to our protocol, can be reduced by more carful optimalization of low molecular heparin administration with a good safety profile. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Meanwhile, some studies have shown that therapeutic doses do not increase the risk of bleeding ( 158 ). However, some studies have avoided an increased dose of thromboprophylaxis due to a slight increase in bleeding events ( 159 , 160 ). The difficulty of using anti-thrombotic therapy during the period of severe and critical illness highlights the importance of timely comprehensive antithrombotic therapy before the late stage.…”
Section: Inhibiting the Prothrombotic Statementioning
confidence: 99%
“…Meanwhile, some studies have shown that therapeutic doses do not increase the risk of bleeding ( 158 ). However, some studies have avoided an increased dose of thromboprophylaxis due to a slight increase in bleeding events ( 159 , 160 ). The difficulty of using anti-thrombotic therapy during the period of severe and critical illness highlights the importance of timely comprehensive antithrombotic therapy before the late stage.…”
Section: Inhibiting the Prothrombotic Statementioning
confidence: 99%
“…A total of 36 articles were included in the pooled analysis ( Table 1 ). 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 The majority (28; 78%) consisted of retrospective cohort studies whereas three (8%) were RCTs and five (14%) were prospective cohort studies ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…LMWH was chosen mainly because of its higher efficacy and comparable safety compared to VKA [12,29]. LMWH remains the best thromboprophylaxis option for hospitalized patients with high risk of incident of VTE [30].…”
Section: Discussionmentioning
confidence: 99%